Contribution of civil construction in the emission of gases involved with greenhouse effect - Furtado, Felipe Casa Nova; Borille, Fátima de Cássia de Athayde; Santos , Andréa de Melo; Monteiro, Eliana Cristina Barreto; de Campos-Takaki , Galba Maria (Seven Editora, 2023)
Civil construction is one of the most important industries in the world, responsible for the creation of housing, infrastructure, and commercial buildings. However, this industry is also a major source of greenhouse gas (GHG) emissions, including carbon dioxide (CO2), which contributes to climate change. In addition, construction is also a source of other air pollutants that contribute to the degradation of the ozone layer. In this context, research conducted with the impacts of civil construction that contribute to the emission of greenhouse gases and degradation of the ozone layer is presented, as well as the development of actions to minimize GHG production by 2030, being a challenge that requires commitment and changes in the culture of the construction industry. Construction has the responsibility and opportunity to lead this change to promote a more sustainable and just future for all. In addition, solutions are presented to minimize the emission of polluting gases in civil construction, highlighting the importance of energy efficiency, the use of alternative materials, and the adoption of efficient and innovative practices in construction and operation, without compromising the quality and structural performance of buildings.DOI:https://doi.org/10.56238/alookdevelopv1-072